2016
DOI: 10.18632/oncotarget.9626
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and proteomic analysis of mouse radiation-induced acute myeloid leukaemia (AML)

Abstract: A combined transcriptome and proteome analysis of mouse radiation-induced AMLs using two primary AMLs, cell lines from these primaries, another cell line and its in vivo passage is reported. Compared to haematopoietic progenitor and stem cells (HPSC), over 5000 transcriptome alterations were identified, 2600 present in all materials. 55 and 3 alterations were detected in the proteomes of the cell lines and primary/in vivo passage material respectively, with one common to all materials. In cell lines, approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The association of IL7 gene and leukemia is mentioned in [61] and [62]. Furthermore, IL7 gene is associated with leukemia related KEGG pathways such as (hsa04630) Jak‐STAT signaling pathway ( p ‐value=4.50E‐05) [71,72], (hsa04060) cytokine‐cytokine receptor interaction pathway ( p ‐value=1.76E‐14) [73], (hsa04151) PI3KAkt signaling pathway ( p ‐value=1.29E‐13) [74–76], and the leukemia disease related GO terms like GO:CCs of extracellular space (GO:0005615) ( p ‐value=1.49E‐33) [83], extracellular region (GO:0005576) ( p ‐value=3.91E‐07) [82], and GO:MF of cytokine activity (GO:0005125) ( p ‐value=1.51E‐10) [84]. Besides that, the PTK2 gene is connected with leukemia as mentioned in [3,68,69].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The association of IL7 gene and leukemia is mentioned in [61] and [62]. Furthermore, IL7 gene is associated with leukemia related KEGG pathways such as (hsa04630) Jak‐STAT signaling pathway ( p ‐value=4.50E‐05) [71,72], (hsa04060) cytokine‐cytokine receptor interaction pathway ( p ‐value=1.76E‐14) [73], (hsa04151) PI3KAkt signaling pathway ( p ‐value=1.29E‐13) [74–76], and the leukemia disease related GO terms like GO:CCs of extracellular space (GO:0005615) ( p ‐value=1.49E‐33) [83], extracellular region (GO:0005576) ( p ‐value=3.91E‐07) [82], and GO:MF of cytokine activity (GO:0005125) ( p ‐value=1.51E‐10) [84]. Besides that, the PTK2 gene is connected with leukemia as mentioned in [3,68,69].…”
Section: Resultsmentioning
confidence: 99%
“…In Ref. [84], authors reported involvement of GO:MF of cytokine activity in leukemia. The association between the GO:CC of extracellular region and leukemia is found in [82].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dysregulation of Jarid2 gene is observed during Kaposi sarcoma-associated herpesvirus infection and leads to cell transformation [ 79 ]. Metap2, on the other hand, is differentially expressed in cells derived from mice developing an acute murine leukemia [ 54 ]. Thus, all these data suggest that P50 could act on several signaling pathways leading to insensitivity to growth inhibitory signals.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this first description of a mouse model of radiation leukemia where it is possible to track leukemogenic events over time from initial exposure to presentation of disease provides a basis from which to study additional factors modulating radiation leukemia incidence. For example, how predisposition in human or mouse, exposure to pathogens, inflammation or calorie restriction can modify mouse radiation leukemia incidence [9,10]. Are the Chr2 deletion and subsequent mutation events directly related to target cell-intrinsic events, or could microenvironment-derived diffusible factors or microvesicle mediation play a role?…”
Section: Tom Verbiest Simon Bouffler and Christophe Badiementioning
confidence: 99%